The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2478/v10042-010-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in thickness of each layer of developing chicken cornea after administration of caffeine.

Abstract: Abstract:The aim of the study was the presentation of changes in thickness of each layer of a developing cornea, that came into being under an influence of caffeine which was administered to chicken embryos. Research materials were 26 chicken embryos from breeding eggs that had been incubated. Breeding eggs were divided into two groups: control (n=30) in which Ringer liquid was given, and experimental (n=30) in which teratogenic dose of caffeine was administrated -3.5 mg/egg. In 36 th hour of incubation soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Caffeine readily crosses the placental barrier and into the milk of nursing mothers [6], and numerous attempts have been made to assess the impact of caffeine on embryonic and foetal development. Many experimental studies on animals have shown teratogenic and embryotoxic effects of high caffeine doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine readily crosses the placental barrier and into the milk of nursing mothers [6], and numerous attempts have been made to assess the impact of caffeine on embryonic and foetal development. Many experimental studies on animals have shown teratogenic and embryotoxic effects of high caffeine doses.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a number of experimental studies it has been proved that caffeine consumption during pregnancy carries a number of side-effects for both the mother and the developing foetus [2,3,4,5,6,7,8,9]. However, in the available literature, no studies have been found relating to the effects of caffeine administered at both low and high temperatures on foetal development.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Saleh et al [36] found that when caffeine levels in serum increased, the number of eggs decreased, which could be connected with the accumulation of caffeine in the follicular fluid. Kujawa-Hadryś et al [37,38] showed that caffeine causes disturbances in the developing cornea in chicken embryos. Additionally, KujawaHadryś et al [38] found that caffeine causes changes to the collagen fibers of Bowman's membrane patterns and to the corneal stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a number of studies have confirmed the negative effect of high doses of caffeine ingested during pregnancy both for the mother and the developing foetus [2,3,7,15,16,18,22,25,27,30,31].…”
Section: Introductionmentioning
confidence: 99%